How Results are Created: Methodological Approaches to the Design of Educational Outcomes - Barannikov K.A; Remorenko I.M (Moscow State University of Psychology and Education, 2020)
The authors make retrospective analyze of "outcome-based education" and "competence-based education" concepts evolution. National educational standards and curricula all around the world have gone through dramatic transformation over the last 20 years. New education models require new methodology for designing educational outcomes. In the paper, based on the analysis of international experience, a framework for designing outcomes is proposed. Authors analyze Canada, UK, Finland, Australia, USA experience. Also terminology of meta-subject and subject outcomes are discusses in the paper. The framework presented by the authors is applicable both for school and teacher curricula, and at the national level, when formulating standards or example currucula.